Design and Hardware Implementation of Combining PD with HSSC for Optimizing Behavior of Magnetic Levitation System - Alrawi, Ali Amer Ahmed; Lilo, Moneer Ali; Al Mashhadany, Yousif (Journal of Robotics and Control (JRC), 2025)
This paper presents the design and implementation of a hybrid control system that uses Proportional-Derivative (PD) and High-Speed Switching Controller (HSSC) methods to enhance Maglev system performance. The goal is to design controllers that properly follow input references and improve system stability and reactivity. The PD controller is fast and easy to install, but it cannot handle system disturbances and nonlinearities, which might cause instability. HSSC integration addresses these issues. The HSSC makes the PD controller more resilient to external forces and nonlinear dynamics. The combined PD-HSSC approach ensures stable levitation, precise positioning control, and system reliability in various conditions. The hybrid system reduced steady-state error and maintained system stability under dynamic input conditions, although it over-shoot more than PD alone. The computer-aided real time simulation of system dynamics is done, and the control rules are formulated out of a combination of PD Control for normal control processes and the HSSC for enhanced robustness. The total control current is given by the algebraic addition of the PD control action going, the equivalent control going, and the switching control going. However, the proposed PD-HSSC technology is possible to provide a stable levitation state for the control of precise position, even in the nonlinear and disturbance conditions The experimental results showed an 89% enhancement in the efficiency of the hybrid control system. The integration of PID (Proportional-Integral-Derivative) and HSSC has been developed in this system using MATLAB Simulink. The real-time findings demonstrate that the PD-HSSC system is higher in stability for operating the maglev system. This is due to its much lower steady-state error compared to the PD system, regardless of the kind of step input or dynamically fluctuating sine and square wave inputs. However, PID_HSSC exhibited a greater degree of overshoot in comparison to the PD.